المظاهر السريرية وأشكال الإصابة الكلوية عند الأطفال المصابين بفرفريه هينوخ شونلاين - ميهوب محمد (Latakia University Journal -Medical Sciences Series, 2014)
يهدف البحث إلى دراسة المظاهر السريرية و أشكال الإصابة الكلوية عند 50 طفلاً راجعوا مستشفى الأسد الجامعي في اللاذقية في الفترة بين 1/1/2007 و 1/1/2012 تراوحت أعمارهم بين سنة و 14 سنة. أظهرت الدراسة أن فرفرية هينوخ شونلاين تصيب الذكور والإناث مع أرجحية إصابة الذكور ((58% على الإناث (42%) و أن المرض يزداد تصادفا في الربيع عند ((40% والشتاء ((36% . كما بينت الدراسة أن المرض جهازياً أكثر ما يصيب الجلد والمفاصل والأمعاء والكلية التي كانت نسبة إصابتها (30%) في المرحلتين الحادة وحالات النكس وتظاهرات الإصابة على شكل بيلة بروتينية ودموية متفاوتة الشدة . This research tends to study clinical manifestation and kinds of kidney illnesses on 50 children visited Al-Assad university hospital in Lattakia from January 1st,2007 to January 1st, 2012 aged between one year to 14 years. The study showed that Henoch Schonlein purpura attack both males and females but attack males more (58% males) (42% females) . This illness increases in spring and winter (40% in spring) ( 36% in winter) . The study also showed that the illness is systemic disease , mostly attacking skin, joints, gastro intrudes and kidney in which the illness has taken place at 30% in the acute stage and De relapsed stage and the symptoms appeared as varying intensity proteinurea and hematurea.